KREATIVITAS PENGGUNAAN MEDIA DARING SEBAGAI SARANA PEMBELAJARAN DI MASA PANDEMI COVID-19 PADA MATA PELAJARAN AKIDAH AKHLAK - SYAFRIWANA, SYAFRIWANA (Dahzain Nur, 2021)
Abstract Moral aqidah subjects at the time of online learning in addition to providing many conveniences and increasing teacher creativity. Creativity in using online media as a learning tool during the COVID-19 pandemic on moral aqidah subjects at Madrasah Aliyah Al-Qamar Bajeng. The informants in this study were students of class XI Madrasah Aliyah Al-Qamar Bajeng. The results of the research that the author did were the creativity of the akidah moral teacher to have creativity, namely making power point slides in which there were interesting pictures, the presentation of other material was also in the form of short videos that contained interesting pictures. easy to access and easy to download and explain the learning material via zoom, this is all so that students are easy to understand and don't get bored easily so that the learning process can flow in the sense that students are active in the learning process even though the learning process is online.